DNA-Damage-Induced Alternative Splicing of p53 - Chen, Jing (Cancers (Basel), 2021)
SIMPLE SUMMARY: The tumor suppressor p53 is frequently mutated across numerous cancer types and has an essential role in the response to DNA-damaging agents, such as irradiation. DNA damage can induce different forms of the p53 protein, and the different forms of the p53 protein can elicit distinct types of cell death. Specifically, the activation of full-length p53 typically results in cellular apoptosis, while the induction of the alternatively spliced isoform, the beta isoform of p53 (p53β), results in cellular senescence. In this report, we review the known roles of p53β and introduce novel insights into p53β function. ABSTRACT: Cellular responses to DNA damage and other stresses are important determinants of mutagenesis and impact the development of a wide range of human diseases. TP53 is highly mutated in human cancers and plays an essential role in stress responses and cell fate determination. A central dogma of p53 induction after DNA damage has been that the induction results from a transient increase in the half-life of the p53 protein. Our laboratory recently demonstrated that this long-standing paradigm is an incomplete picture of p53 regulation by uncovering a critical role for protein translational regulation in p53 induction after DNA damage. These investigations led to the discovery of a DNA-damage-induced alternative splicing (AS) pathway that affects p53 and other gene products. The damage-induced AS of p53 pre-mRNA generates the beta isoform of p53 (p53β) RNA and protein, which is specifically required for the induction of cellular senescence markers after ionizing irradiation (IR). In an attempt to elucidate the mechanisms behind the differential regulation and apparent functional divergence between full-length (FL) p53 and the p53β isoform (apoptosis versus senescence, respectively), we identified the differential transcriptome and protein interactome between these two proteins that may result from the unique 10-amino-acid tail in p53β protein.